Responding to Covid-19 via online learning: the relationship between Facebook intensity, community factors with social capital and academic performance - Ahmed, Mohemed Idries; Mustaffa, Che Su; Abdul Rani, Nur Shazana (PalArch Foundation, 2020)
The rapid adoption of social media technologies has resulted in a fundamental shift in the way communication and collaboration take place. As staff and students use social media technologies in their personal lives, it is important to explore how social media technologies are being used as an educational tool especially during a pandemic where teaching and learning has to be done via mediated communication. However, the question arises as to how effective the use of social media in terms of Academic Performance and Social Capital of the students. Academic Performance and Social Capital of university students are two interrelated and critical issues which can define the efficacy of social and academic activities of students at their universities. However, few studies have adopted a holistic approachto determine the direct role of online social network activities such as Facebook Intensity, and Community Factors on both Academic Performance and Social Capital of university students. Thus, this study attempted to conduct a cross-sectional survey using self-administered questionnaires which were distributed to 518 undergraduate students at the University of Sirte, Libya. The data was analyzed using various analytical techniques including descriptive statistics, preliminary and inferential analyses by using SPSS and PLS-SEM. The results revealed that Facebook Intensity and Community Factors significantly relate to Social Capital and Academic Performance. This study concludes that the intensity of Facebook Usage among university students and the interactions maintained by students can be used to develop Social Capital. Also, university students with good social communications skills and high self-esteem will benefit from interactions with lecturers and peers and these benefits will certainly enhance their Academic Performance. This study also demonstrates the potential of using Facebook as a teaching aid during pandemic.